LINC00473 regulated apoptosis, proliferation and migration but could not reverse cell cycle arrest of human bone marrow mesenchymal stem cells induced by a high-dosage of dexamethasone - Yingxing Xu (Stem Cell Research, 2020)
Dysfunction of bone marrow mesenchymal stem cells (BMSCs) is involved in the pathogenesis of steroid-induced osteonecrosis of the femoral head (SONFH). Long noncoding RNAs (lncRNAs) contribute to biological effects exerted on BMSCs by regulating the expression of genes. However, most recent studies have focused on the role of lncRNAs in modulating the imbalance between osteogenic and adipogenic differentiation but not apoptosis, proliferation, cell cycle and migration of BMSCs, especially in Dex-treated BMSCs. In this study, we conducted a microarray analysis to investigate the differential expression profiles of lncRNAs between human BMSCs (hBMSCs) obtained from patients with SONFH and control patients with femoral neck fracture. The microarray analysis showed that a total of 48 differentially expressed lncRNAs were identified in hBMSCs between the two groups, including 24 upregulated lncRNAs and 24 downregulated lncRNAs. Among of them, LINC00473 was found to be significantly downregulated. In the following study, we found that 10−6 mol/L Dex significantly inhibited proliferation, arrested cell cycle at the G1 phase, increased caspase-3 activity, induced apoptosis and impeded the migration of hBMSCs, while downregulation of the expression of LINC00473 produced results that were in line with the results of the microarray analysis in a time-dependent manner. Interestingly, upregulation of LINC00473 attenuated the negative effects caused by 10−6 mol/L Dex on hBMSCs, except for cell cycle arrest. Furthermore, it should be noted that LINC00473 had no effect on the proliferation and cell cycle of hBMSCs in the absence of Dex. Collectively, our data revealed that LINC00473 attenuated apoptosis, promoted the proliferation and migration of Dex-induced hBMSCs, which are not involved in interference with the cell cycle of hBMSCs.